STEM learning design to train student’s system thinking skills on climate change - Anis Shofatun; Elly Herniani; Dinny Mardiani (University of Muhammadiyah Malang, 2024)
Climate change in coastal areas is a complex problem that involves value systems and requires various scientific disciplines. Integration of Science, Technology, Engineering and Mathematics (STEM) approach is needed in learning so that it can train students to think holistically, structured and systematically. This research was carried out with the aim of producing an appropriate STEM learning design to train students' systems thinking skills on climate change material. The type of research is research and development using the analysis, design, development, implementation and evaluation (ADDIE) model. The trial subjects in this research were 28 class VIII students of SMP Muhammadiyah 12 GKB Gresik, East Java. The research instruments were validation sheets of lesson plan and student worksheets, observation sheets, and systems thinking skills assessment sheets. The research results show; (1) The Extraordinary Lesson Plan (ELP) and student worksheet of STEM learning design development which are measured through Aiken Validity with a value of 0.89 ≥ 0.6 in the valid category; (2) The STEM learning design developed is in the practical category with an average score of 3.5; and (3) students' systems thinking abilities in climate change material are in the good category. It can be concluded that the STEM learning design developed to train junior high school students' systems thinking skills was feasible to be used in learning.